Analisis Peramalan dan Optimalisasi Persediaan Maklon Skincare dengan Metode EOQ, ROP, dan Safety Stock - Muhammad Zidane Elang Syah Putra; Hastawati Chrisna Suroso (Universitas Muhammadiyah Surabaya Publishing, 2026)
This study aims to analyze demand forecasting and optimize inventory control for 12.5g day cream products at a skincare maklon company, PT. KSM. The methods employed include demand forecasting using Moving Average, Exponential Smoothing, and Linear Trend approaches, as well as inventory optimization using Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock. The data utilized consist of two years of demand data, ordering costs, holding costs, and lead time. The results indicate that the Linear Trend method provides the highest accuracy, with MAD of 590.894, MSE of 485,888.3, and MAPE of 41.48%. Based on the forecasting results, the optimal EOQ is 1,160 units with an ordering frequency of 11–12 times per year, a Safety Stock of 15 units, and an ROP of 202 units. The implementation of these methods results in a total annual inventory cost of IDR 11,748,012, which is more efficient compared to the previous system. Additionally, the ordering frequency is reduced, and the risks of stockout and overstock are minimized. Therefore, the integration of forecasting and inventory control methods is proven to enhance operational efficiency and support more effective decision-making in inventory management within the skincare maklon industry.